Numerical and theoretical study on the jacking force prediction of slurry pipe jacking traversing frozen ground. (September 2021) - Wen, Kai; Zeng, Wei; Shimada, Hideki; Sasaoka, Takashi; Hamanaka, Akihiro
Highlights: Considering the pipe-lubricant-frozen soil interaction of pipe jacking in frozen ground. Discussing the shear stress among pipes, lubricant and frozen soil. Proposing a new calculation model to predict the jacking force in frozen ground. Investigating the monitoring data to adequately validate the calculation model. The proposed prediction model is more suitable to estimate the jacking force of pipe jacking in frozen ground. Abstract: Jacking force is a controlling factor in design and construction of pipe jacking. To date, there is few researches focused on prediction of jacking force in frozen ground. Therefore, this paper investigates the main geotechnical issues, including the jacking force and pipe-soil interaction of pipe jacking in frozen ground. Firstly, a series of numerical simulations and comparative analyses with theoretical solutions were conducted to discuss the surface friction force. Then, a new calculation model of jacking force under different pipe-soil interactions and characteristics of the frozen ground was proposed by considering the impact of temperature and the static friction rather than sliding friction. Finally, compared with the measured data obtained from pipe jacking operation in frozen ground in Japan, the jacking force predicted by using the proposed calculation model agreed well with the measured data. The new calculation model can simulate the jacking force in frozen ground more precisely than the conventional ones. The conclusions of this paper would provide reference for prediction of pipe jacking force in frozen soil area.